Odpowiedzi

2009-12-09T18:50:18+01:00
2a +(3a+4b+3) =
=2a+3a+4b+3=
=5a+4b+3

(x+9y+9) + ( x -9y + 9)=
=x+9y+9+x-9y+9=
=2x+18
<y się zredagują>

(3x - 3y +2z) + (-2x +3y-z)=
=3x-3y+2z-2x+3y-z=
=x-z
<y się zredagują>
2009-12-09T18:51:27+01:00
2a +(3a+4b+3) =2a+3a+4b+3=5a+4b+3

(x+9y+9) + ( x -9y + 9)=x+9y+9+ x -9y + 9=2x+18

(3x - 3y +2z) + (-2x +3y-z)=3x - 3y +2z-2x +3y-z=x+z


2009-12-09T18:52:25+01:00
A) 2a +(3a+4b+3) =2a+3a+4b+3=5a+4b+3
b) (x+9y+9) + ( x -9y + 9)=x+9y+9+x-9y+9=2x+18
c) (3x - 3y +2z) + (-2x +3y-z)= 3x-3y+2z-2x+3y-z=x+z